2021
DOI: 10.1039/d0qm00563k
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazoloanthrone-functionalized fluorescent copolymer for the detection and rapid analysis of nitroaromatics

Abstract: The development of sensors for rapid detection of chemical explosives with high sensitivity and selectivity is the focus of many research groups. In this work, we have developed a simple...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The absorption spectrum of Cl-dye-OH shows π → π* transitions at 280 nm and an intramolecular charge-transfer (ICT) band at 415 nm. 21 Similar transitions were observed in the dye-functionalized polymers indicating that the conjugation to the polymer did not alter the electronic properties of the dye, which was expected as the coupling site was decoupled from the conjugated system of the dye (Fig. 4).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…The absorption spectrum of Cl-dye-OH shows π → π* transitions at 280 nm and an intramolecular charge-transfer (ICT) band at 415 nm. 21 Similar transitions were observed in the dye-functionalized polymers indicating that the conjugation to the polymer did not alter the electronic properties of the dye, which was expected as the coupling site was decoupled from the conjugated system of the dye (Fig. 4).…”
Section: Resultssupporting
confidence: 58%
“…19 Yang Hu et al reported the synthesis of a fluorometric fluoride ion probe, based on anthra[1,9- cd ]pyrazol-6(2 H )-one. 20 Recently, Saravanan et al 21 developed copolymers functionalized with anthrapyrazolone derivatives that were successfully used for the detection of nitroaromatic compounds and other explosive analytes. Moreover, polymeric microparticles were reported for simultaneous adsorption and fluorescence detection of hazardous Cr( vi ) ions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 59 ] Generally, a lower LUMO energy level of the acceptor facilitates accepting electron transfer from the donor. [ 60 ] Herein, the energy levels of all tested antibiotics were calculated and arranged in a descending order, which could show the possibility and degree of electron transfer from electron‐rich sensor to the electro‐deficient analytes in the luminescent quenching process (Figure 7f). Obviously, the five NAAs possessed lower LUMO energy levels among all antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…p-NT molecules may probably be adsorbed on the surface of complex 1, and the luminescence quenching of 1 might be due to a photoinduced electron-transfer mechanism. 53,54 While the benzene rings in the main frame of 1 are enriched with rich p-electron clouds, the LUMO energies of p-NT are low-lying p*-type orbitals stabilized by the -NO 2 group. This can force the electrons to transfer from 1 to the LUMO of p-NT, thus leading to the luminescence quenching.…”
Section: Fluorescence Sensing Toward Explosivesmentioning
confidence: 99%